Investigation of non linear dynamics of an excitable magnetron sputtering plasma - Gopikishan Sabavath; Pankaj Kumar Shaw; A.N. Sekar Iyengar; I. Banerjee; S.K. Mahapatra (Results in Physics, 2019)
In this paper nonlinear dynamical behaviour of an excitable DC magnetron sputtering plasma has been investigated. Initially, plasma exhibited fixed point dynamics whereas with the increase in the discharge voltage, spikes were observed in the floating potential fluctuations. Furthermore, the increasing of discharge voltage resulted the increase in spikes. Power spectrum plot, normalized variance, recurrence plot and Hurst exponent are employed to extract the underlying feature of the floating potential fluctuations. A dip in the plot of normalized variance with variation in the control parameter has been seen, which is strongly indicative of coherence resonance like behaviour in the system. Power spectrum plot and Hurst exponent estimation are confirming the presence of coherence resonance behaviour. Apart from quantitative confirmation, visual verification of coherence resonance behavior has been carried out using recurrence plot analysis. It is noticed that the noise component increases with the increase in the discharge voltage and a suitable intrinsic noise strength plays an important role in generating the coherence resonance. Keywords: Intrinsic coherence resonance, Floating potential fluctuation, DC magnetron plasma, Hurst exponent, Noise component